Elicitation strategies of in-vitro cultures for the sustainable use of medicinal plants: Elicitation Strategies of in vitro cultures - Khan, Tariq; Abbasi, Bilal Haider; Khan, Mubarak Ali (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2019)
Medicinal plants are highly traded for its promising potential against different types of diseases including cancers. Development of elicitation strategies for increased production of important anticancer compounds from invitro cultures of medicinal plants has proved very productive. For this purpose, different stresses are applied to invitro cultures to produce increased amounts of the compounds. For instance, cell cultures are produced via stem explants in the Murashige & Skoog basal medium supplemented with different concentrations of plant growth regulators (PGRs). The extracts from samples are then subject to flavonoid and phenolic content assessment, antioxidant quantification and Chromatographic analysis. In our experiments, among the many PGRs, Thidiazuron (TDZ) triggered higher quantities of biomass and total flavonoid & phenolic content (191.03 μg quercetin/mg and 202.8 μg gallic acid equivalent/ mg, respectively) through cell cultures of F. indica. Similarly, sucrose induced the maximum biomass among the different carbon sources (fructose, glucose, maltose, and sucrose) given in different concentrations to cell cultures of F. indica while glucose produced the maximum phenolic content followed by fructose when harvested after 42 days. Manipulation in the supply of light to the cultures with a combined effect from other chemicals, a significant effect was seen on growth and secondary metabolism such that dark-grown cell cultures treated with Methyl Jasmonate (Me-J) gave the highest TPC. High-performance liquid chromatography analysis revealed an increased quantity of secondary metabolites. In conclusion, cell cultures of F. indica treated with Thidiazuron and grown in dark in the presence of glucose as a sugar source and Me-J as elicitor gives enhanced quantities of important anticancer secondary metabolites.